2016
DOI: 10.5897/ijlp2016.0298
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Haematological Parameters of Rabbits fed graded levels of Bitter kola (Garcinia kola)

Abstract: The need to reduce cost of production of meat animal has necessitated the use of plant materials with medicinal properties as feed additives capable of minimizing the influence of pathogenic microbes and improving performance of the animal. This study investigated the effect of such medicinal plant materials Garcinia kola on the growth performance and the haematological parameters of 20 weeks old rabbits. Thirty six rabbits of mixed breed and mixed sexed were used for the experiment, which lasted for eight wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…Hence, the lower RBCs and Hb values recorded for the control rabbits may be due to the stress associated with anti-nutritional factors, which often cause depletion in the oxygen-carrying capacity of the animal's blood, leading to an impaired growth response [61]. Our result is contrary to the findings of Ebenebe et al [51], who reported a reduction in the Hb values among rabbits fed with GKS diets. The reports of Udenze et al [58] also did not align with our current findings.…”
Section: Hematological Indicescontrasting
confidence: 98%
See 2 more Smart Citations
“…Hence, the lower RBCs and Hb values recorded for the control rabbits may be due to the stress associated with anti-nutritional factors, which often cause depletion in the oxygen-carrying capacity of the animal's blood, leading to an impaired growth response [61]. Our result is contrary to the findings of Ebenebe et al [51], who reported a reduction in the Hb values among rabbits fed with GKS diets. The reports of Udenze et al [58] also did not align with our current findings.…”
Section: Hematological Indicescontrasting
confidence: 98%
“…Rabbits that received higher dietary levels (3% and 4.5%) of GKSM had reduced ADWG than the control (Table-4). Ebenebe et al [51] reported that as the dietary inclusion levels of G. kola increased from 2.5% to 7.5%, the weight gain of the rabbits was significantly depressed. Higher levels of GKSM had been previously reported to have growth-depressing effects on rabbits [31,52] and broiler birds [30].…”
Section: Growth Performance Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood indices are major tools for assessing the physiological, pathological and nutritional status of animals. Haematological traits are strongly influenced by diets and the existence of the correlation between performance and haematological traits has been reported by Ebenebe, Nwankwor, Izukanne, and Ufele (2016). Also, the immunomodulatory properties of herbs were reported by Oloruntola et al (2016b).…”
Section: Effects Of Phyto-additives On Haematological Indices Of Brmentioning
confidence: 88%